A relevância do Marketing Digital para empresa do setor gráfico: estudo de caso em uma empresa gráfica em Manaus - Regis, Lígia Ribeiro (Brasil, 2024)
The emergence of social networks has become one of the most important tools in the area of marketing, as it helps to create a positive image in the company and if it is developed from a planning supported by strategies to influence consumers through interaction and the desire to purchase the product of their interest. The general objective of this study is to analyze the relevance of digital marketing for a company in the printing sector located in Manaus. The research was carried out at the printing company S.G.C.V. The data collection procedure is given by an on-site visit to the company, where an open interview was conducted with the company's manager, where he was cordially informed about the company. Questions were asked to construct the SWOT analysis, GUT Matrix and consequently to elaborate the 5W2H. The present research made it possible to propose an action plan to enhance the company's marketing. He analyzed that the company had a great difficulty because it did not have a digital marketing team, and an intervention process was essential. In this context, quality tools were used to obtain the priority for action. In this way, it was suggested through an action plan through the 5w2h tool to hire an outsourced digital marketing company based on this research.